Optimizing the Performance of a Converter Dc/Dc in a Photovoltaic System - N. Mazouz; A. Midoun (Algerian Journal of Research and Technology (AJRT), 2021)
The objective of this scientific research is the development of DC / DC converters for optimizing the efficiency of a photovoltaic system, as to find the most accurate mathematical modeling possible to predict behavior, and to provide Measurable information related to the physical quantities of the system. The search for the maximum power point is the essential work in the optimization of photovoltaic systems because there is a problem of adaptation between the load characteristics and the maximum power point of the photovoltaic generator. The optimization deals with the electrical operating parameters of the solar generator. A photovoltaic generator can operate in a wide range of voltage and output current but it can deliver maximum power only for particular values of current and voltage. , thus the realization of an experimental prototype for the characterization of the converter using different control techniques VMC (Voltage Mode Control) and PCM (Peak Current Mode).